Quantification of microvascular cerebral blood flux and late‐stage tumor compartmentalization in 9L gliosarcoma using flow enhanced MRI. (21st January 2013) - Reynaud, Olivier; Geffroy, Françoise; Ciobanu, Luisa
Abstract : Measurements of tumor microvasculature are important to obtain an understanding of tumor angiogenesis and for the evaluation of therapies. In this work, we characterize the evolution of the microvascular flux at different stages of tumor growth in the 9L rat brain tumor model. The absolute quantification of cerebral blood flux is achieved with MRI at 7 T using the flow enhanced signal intensity (FENSI) method. FENSI flux maps were obtained between 5 and 14 days after glioma cell inoculation. Based on cerebral blood flux maps, we highlighted two main stages of tumor growth, below and above 3 mm, presenting distinct flux patterns and vascular properties. No significant difference emerged from the group analysis performed on the data collected at an early developmental stage (tumor size < 3 mm) when compared with healthy tissue. At a late developmental stage (tumor size > 3 mm), we observed a significant decrease in the cerebral blood flux inside the gliosarcoma (−33%, p < 0.01) and compartmentalization of the tumor ( p < 0.05). FENSI flux maps delineated a low‐flux tumor core (58 ± 17 μL/min/cm 2 ) and higher vascularized regions around the tumor periphery (85 ± 21 μL/min/cm 2 ). Histology was performed on 11 animals to finely probe the intratumor heterogeneity and microvessel density, and the results were compared with the information derived from FENSI flux maps. The hyper‐ and hypoperfused tumor regions revealed with FENSI at the late tumor developmental stage correlated well with the ratios of high and low blood vessel density ( R 2 = 0.41) and fractional vascular surface ( R 2 = 0.67) observed with fluorescence microscopy [cluster of differentiation 31 (CD31) staining]. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Quantitative microvascular blood flux maps obtained at different developmental stages of the 9L rat brain tumor model using the magnetization transfer‐free flow enhanced signal intensity (FENSI) technique highlight distinct flux patterns and vascular properties. Late‐stage measurements highlight a significant decrease in flux inside the gliosarcoma (−33%, p < 0.01) and tumor compartmentalization ( p < 0.05). The hyper‐ and hypoperfused tumor regions revealed with FENSI correlate well with ratios of high and low blood vessel concentration and microvascular area revealed with immunohistochemistry.